(untitled) (Research, Society and Development, 2025)
Acute coronary syndrome (ACS) has a wide and variable clinical spectrum, with patients suspected of having anything from anginal equivalents such as epigastralgia, cervicobrachial paresthesia, dyspnea, to typical chest pain or even, in a more nefarious scenario, cardiorespiratory arrest (CA). Cardiovascular diseases are the biggest cause of morbidity and mortality worldwide and ACS is usually the first manifestation of this. The distinction between high-risk unstable angina, which often requires an invasive approach with cardiac catheterization, and low- to moderate-risk angina, for which various non-invasive stratification tools can be applied, is extremely important. This article aims to explore, through a bibliographic review, the various diagnostic strategies in the context of stable and unstable coronary artery disease (CAD) with low to moderate risk. Given that cardiovascular disease is the leading cause of mortality worldwide and that stable and unstable angina at low to moderate risk have a wide range of stratification methods, the aim of this study is to carry out a literature review of the main validated graphic methods, analyzing their main tools - advantages, disadvantages, sensitivity and specificities - and their application in the context of unstable angina at moderate risk and stable angina.